Drug quality and safety issues in India - Maulik Chokshi; Rahul Mongia; Vasudha Wattal (Indian Council for Research on International Economic Relations (ICRIER), 2015)
Today, the global pharmaceutical product value chain is becoming increasingly complex and this has led to the emergence of 'multiple quality standards' for medicines. But this non-uniformity in the quality of medicine is also contingent upon both the regulatory milieu in the country of manufacture and the export destination of a pharmaceutical product. The focus of this paper is upon the domestic pharmaceutical market in India, where policy makers often face a trade-off between what has been called 'high quality' and 'affordable quality' medicines. With India being recognised as the pharmacy of the developing world, it is believed that there is need for strict quality specification and enforcement within the country in the first place. Against this background, there have been several reports where doubts have been raised regarding quality of medicines available in India. This paper, by mapping the perspectives of several stakeholders, attempts to bring clarity on issues related to poor quality medicines and suggest institutional reforms in the Indian regulatory regime, looking at good and bad practices followed both domestically and internationally.
Keywords: I15; I18; L51; L65; 330; Regulation; Public Health; Government Policy; Pharmaceuticals Manufacturing; Economic Development